Pengaruh Penggunaan Media Busy Board terhadap Kemampuan Motorik Halus Anak Usia Dini - Sari, Purnama; Sukendro; Ismiatun, Asih Nur (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
This study examines the effect of using Busy Board media on the fine motor skills of children aged 4–5 years at TK Negeri 15 Mendalo, Muaro Jambi. The research employed a quantitative approach with a pre-experimental one-group pretest-posttest design, involving 11 children selected through purposive sampling. Initial observations indicated that the children's fine motor development was not yet optimal, as shown by difficulties in drawing, coloring, and writing, particularly in hand-eye coordination. Data were collected through observation sheets and documentation, and analyzed using normality tests, homogeneity tests, and hypothesis testing. The results of the paired sample t-test showed a significant effect of Busy Board usage on children’s fine motor skills (t = 31.894 > tₜable = 2.228; p < 0.05), with an effect size of 4.41, categorized as very strong. These findings indicate that the Busy Board is an effective and recommended medium for stimulating fine motor skills in early childhood. Further research is suggested to examine the effectiveness of Busy Board in larger and more diverse populations.